Criminological analysis of criminal radicalism state among convicts in penal institutions - P. Yu. Danylchenko (Law and Safety)
The article is devoted to the study of the criminal radicalism state among prisoners in penal institutions. The purpose of the article is to formulate a theoretical model of the criminal radicalism state among prisoners in penal institutions.